1999
DOI: 10.1080/096382899297198
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of elderly patients in rehabilitation: stroke versus hip fracture

Abstract: There is a difference in the nature of the stroke and HF events. When either event involves an elderly patient with a broad range of limitations and diseases, a new medical condition develops. In this condition the symptoms of depression and the functional state at admission and upon discharge are not significantly different between these groups of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 5 publications
0
9
0
3
Order By: Relevance
“…Socioeconomic impacts of hip fracture are two-fold. On one hand, hip fracture increases the morbidity and mortality in the elderly [2][3][4]; on the other hand, it is a substantial source of health care expenditure [5,6]. 18-33% of older hip fracture patients die within one year following their fracture [7][8][9][10][11][12][13][14][15], 15-25% require longterm nursing home care or institutionalization [16], and approximately 50% can neither walk independently nor achieve their previous level of independent living [8,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Socioeconomic impacts of hip fracture are two-fold. On one hand, hip fracture increases the morbidity and mortality in the elderly [2][3][4]; on the other hand, it is a substantial source of health care expenditure [5,6]. 18-33% of older hip fracture patients die within one year following their fracture [7][8][9][10][11][12][13][14][15], 15-25% require longterm nursing home care or institutionalization [16], and approximately 50% can neither walk independently nor achieve their previous level of independent living [8,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…First, 1 study showed that depression was more common after stroke than other physical illnesses with similar levels of physical disability 13 ; however, other studies have not corroborated these findings. 14,15 Second, PSD has been observed in individuals with anosognosia. 16 Third, late-onset depression has been associated with white matter disease and small silent infarcts.…”
Section: February 2017mentioning
confidence: 99%
“…Depresivno raspoloženje, depresivne misli bezvrijednosti i beznađa sve do suicidalnih razmišljanja predstavljaju direktan otpor mjerama rehabilitacije i neophodnim promjenama životnog stila [12]. Utvrđeno je da prisustvo depresije nakon moždanog udara ima negativan uticaj na: oporavak kognitivnih funkcija, oporavak sposobnosti za obavljanje životnih aktivnosti i potreba, te povećava rizik od smrtnosti.…”
Section: Uvodunclassified